Investment Literacy as a Strategy to Enhance Financial Independence and Economic Resilience among Academicians in Thailand - Putikadea, Insyirah; Permatasari, Ika; Laksono, Bayu Rama; Permatasari, Intan Kurnia (International Journal of Community Service (IJCS), 2025)
The recent trends in the global financial instruments provide innovation as well as diversification. The digitalisation of finance has made investment opportunities more accessible, but simultaneously brought new problems, especially to retail investors who might lack the financial literacy to assess the risks of the market and identify fraudulent investment offerings. However, the lack of understanding of financial management and investment practices also happens among academics. This study aims to strengthen investment literacy for creating a base of financial independence and economic well-being among the students and lecturers of the Institute of Science, Culture, and Innovation at Rajamangala University of Technology Krungthep (RMUTK) in Thailand. Using a participatory framework, the project was developed in five consecutive steps: problem identification, reference and gap analysis, solution design, implementation, and evaluation. The results indicated that there was a significant improvement in the knowledge and awareness of the participants about financial and investment concepts, most importantly ability to distinguish between savings and investments and the understanding of such investment instruments such as mutual funds, bonds, exchange-traded funds (ETFs), and digital assets. Further, it showed increased confidence in the students and lecturers regarding their personal finance management and their distribution of income to investment.